Pelayanan Fiskus, Sosialisasi, dan Reformasi Perpajakan dalam Meningkatkan Kepatuhan Wajib Pajak: Pengaruh Sanksi Pajak sebagai Variabel Moderasi - Succi Rahmadian; Muhammad Rifaldi; Tiolina Evi Nausta Pardede (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the effects of tax authority services, tax socialization, and tax reform on individual taxpayer compliance in the Jabodetabek region, with tax sanctions as a moderating variable. The study employs a quantitative approach with a sample of 175 Generation Z individual taxpayers selected using stratified random sampling. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that tax authority services, tax socialization, and tax reform have a positive and significant effect on taxpayer compliance. However, the moderation analysis reveals that tax sanctions do not significantly strengthen the relationship between these variables and taxpayer compliance. These findings suggest that Generation Z’s tax compliance is more strongly influenced by service quality, the effectiveness of tax socialization, and the convenience and modernization of the tax system than by the enforcement of sanctions. This study highlights the importance of strengthening service strategies and tax reforms that are adaptive to the characteristics of Generation Z, particularly through the utilization of efficient and user-oriented digital technologies. Practically, the results of this study may serve as a reference for the Directorate General of Taxes in formulating policies and designing more effective tax services to enhance compliance among Generation Z individual taxpayers.